Twinning arrangements and service delivery in Zimbabwe’s local authorities: the case of Bulawayo City Council (Zimbabwe) and eThekwini Municipality (South Africa) - Chilunjika, Alouis; Chilunjika, Sharon R. T (AOSIS, 2022)
The Zimbabwean local government environment has been affected by chronic defects in the provision of basic public services. As such, city twinning has been adopted as one of the strategies to address the impasse in service delivery as it allows for the sharing of expertise in local governance, development, strategic international relations and the enhancement of service delivery in local authorities. Using the exploratory case study research design the study explores the impact the twinning arrangement between Bulawayo City Council (BCC) and eThekwini Municipality and how it has enhanced service delivery in Bulawayo. Data was gathered from written documents, observations and in-depth interviews. The study established that the BCC-eThekwini cooperation has been very fruitful and Bulawayo City Council has benefited immensely through the exchange of ideas and information as well as technology transfer among others from this twinning arrangement. Nonetheless, it was also observed that weak legal and financial frameworks hinders the city twinning partnership from realising its full fruition. The study concluded that city twinning between BCC and eThekwini is a favourable route for creating sustainable South to South linkages that benefit developing cities. As recommendations, the article argues that there is need for clarity in defining the partnership roles and goals, community involvement as well as an enabling policy and institutional environment.